Evaluación de impactos del proyecto de vinculación de la carrera de agronomía en los cinco sectores priorizados en base a indicadores sociales, económicos y ambientales en la provincia de Cotopaxi 2017-2020. - Chanaluisa Choloquinga, Carmen Jasmin (2020)
The present investigation was performed in five sectors prioritized in Cotopaxi province: Cusubamba, Canchagua, Pastocalle, Mulalo and Guaytacama, with the objective of evaluating impacts at the start of the project of linking the Agricultural Engineering Major and at the end of the investigation on the basis of sustainability indicators of social, economic and environmental goals. The percentage in the project intervention is the 90% positive and 9.8 percent, is negative that we must improve in the students' work in the communities. In the economic dimension to start the project of binding has a value of 50.6%, at the end of the investigation has 64.7%, having an increase of 14.1%, in the environmental dimension to start the project of linkage is of 52.5%, at the end of the investigation has 62.7%, having an increase of 10.2%, and the social dimension to initiate the investigation has a value of 48.5%, at the end of the investigation has 61.4%, having an increase of 13%. In the draft link if you have improved the social conditions, economic and environmental sector.